Analyzing Writing Errors on Narrative Texts Made by Grade Nine Students’ of SMP IT Qurrata A’yun Palu - Maghfira, Maghfira; Hastini, Hastini (Journal of General Education and Humanities, 2024)
Students often struggle with grammatical accuracy when writing in English as a second language. This study investigates the types and frequencies of errors made by ninth-grade Indonesian students in their English narrative compositions. The research objectives were to 1) identify common error categories within student-generated narrative texts and 2) determine which error type occurs most frequently. The study utilized a descriptive qualitative approach. Ninth-grade students at SMP IT Qurata’Ayun Palu were assigned a narrative writing task on a designated topic. The collected texts were analyzed using Dulay, Burt, and Krashen's (1982) surface approach error taxonomy. Results indicated a total of 70 errors across the students' work. The most prevalent error type was misformation (50%), followed by omission (36%), addition (13%), and misordering (1%). These findings suggest that difficulties applying correct grammatical forms are a significant obstacle to accurate narrative writing for these students.